Maximum Permissible Integration Capacity of Renewable DG Units Based on System Loads - Dogansahin, Kadir; Kekezoglu, Bedri; Yumurtaci, Recep; Erdinc, Ozan; Catalao, Joao P. S. (MDPI, 2018)
Increasing demand for electricity, as well as rising environmental and economic concerns have resulted in renewable energy sources being a center of attraction. Integration of these renewable energy resources into power systems is usually achieved through distributed generation (DG) techniques, and the number of such applications increases daily. As conventional power systems do not have an infrastructure that is compatible with these energy sources and generation systems, such integration applications may cause various problems in power systems. Therefore, planning is an essential part of DG integration, especially for power systems with intermittent renewable energy sources with the objective of minimizing problems and maximizing benefits. In this study, a mathematical model is proposed to calculate the maximum permissible DG integration capacity without causing overvoltage problems in the power systems. In the proposed mathematical model, both the minimum loading condition and maximum generation condition are taken into consideration. In order to prove the effectiveness and the consistency of the proposed mathematical model, it is applied to a test system with different case studies, and the results are compared with the results obtained from other models in the literature.
Keywords: renewable energy; distributed generation; maximum permissible capacity; POWER DISTRIBUTION NETWORKS; VOLTAGE STABILITY; PLACEMENT; LOSSES; IMPACT; MINIMIZATION; RELIABILITY; STRATEGIES; Energy & Fuels